1997
DOI: 10.1016/s0168-6445(97)00030-2
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated environments in the subsurface and bioremediation: organic contaminants

Abstract: Due to leakages, spills, improper disposal and accidents during transport, organic compounds have become subsurface contaminants that threaten important drinking water resources. One strategy to remediate such polluted subsurface environments is to make use of the degradative capacity of bacteria. It is often sufficient to supply the subsurface with nutrients such as nitrogen and phosphorus, and aerobic treatments are still dominating. However, anaerobic processes have advantages such as low biomass production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
(59 reference statements)
0
21
0
2
Order By: Relevance
“…In relation to the dissolved oxygen (DO) content, O 2 consumption was detected only in the experiment with B. thuringiensis, which is the strain with the highest growth rate. Oxygen concentration is a limiting factor for aerobic bacteria growth and for the decomposition of petroleum hydrocarbons by enzymatic cleavage (oxygenases) of their aromatic rings 11,35 , whose products are used in energy generation pathways 11,36 . Deng et al 37 , when investigating the potential of petroleum hydrocarbons degradation by Achromobacter sp, observed that the highest degradation rate occurred during reactor media agitation, thus allowing sufficient oxygen transfer and maintaining the optimum DO levels for biodegradation.…”
Section: Morphological and Molecular Characterization Of Isolated Bacmentioning
confidence: 99%
“…In relation to the dissolved oxygen (DO) content, O 2 consumption was detected only in the experiment with B. thuringiensis, which is the strain with the highest growth rate. Oxygen concentration is a limiting factor for aerobic bacteria growth and for the decomposition of petroleum hydrocarbons by enzymatic cleavage (oxygenases) of their aromatic rings 11,35 , whose products are used in energy generation pathways 11,36 . Deng et al 37 , when investigating the potential of petroleum hydrocarbons degradation by Achromobacter sp, observed that the highest degradation rate occurred during reactor media agitation, thus allowing sufficient oxygen transfer and maintaining the optimum DO levels for biodegradation.…”
Section: Morphological and Molecular Characterization Of Isolated Bacmentioning
confidence: 99%
“…The amount of natural crude oil seepage was estimated to be 600,000 metric tons per year with a range of uncertainty of 200,000 metric tons per year [1]. Release of hydrocarbons into the environment whether accidentally or due to human activities is a main cause of water and soil pollution [2]. Soil contamination with hydrocarbons causes extensive damage of local system since accumulation of pollutants in animals and plant tissue may cause death or mutations [3].…”
Section: Introductionmentioning
confidence: 99%
“…The refining processes of crude oil into petroleum products are the main sources of man-induced hydrocarbons. Release of hydrocarbons into the environment whether accidentally or due to human activities is a main cause of water pollution [26].…”
Section: Resultsmentioning
confidence: 99%